Chapter Educare alle relazioni e alla sessualità: il ruolo della scuola nel promuovere il benessere e prevenire la violenza di genere e l’omofobia - Scierri, Irene Dora Maria (Firenze University Press, 2025)
The contribution illustrates the role of relationship and sexuality education in promoting health and well-being among young people and preventing gender-based violence and homophobia.